The effect of endoscopic variceal eradication on portal hypertensive gastropathy - Hülya ÖVER; Aylin OKÇU; Yasemin KOŞAR; Uğur YILMAZ; Özden TULUNAY; Aysel ÜLKER (Turkish Journal of Gastroenterology, 2019)
-